2016
DOI: 10.1002/ajmg.a.37771
|View full text |Cite
|
Sign up to set email alerts
|

Update on the ACTG1‐associated Baraitser–Winter cerebrofrontofacial syndrome

Abstract: Baraitser–Winter cerebrofrontofacial syndrome is caused by heterozygous missense mutations in one of the two ubiquitous cytoplasmic actin‐encoding genes ACTB and ACTG1. Recently, we characterized the large cohort of 41 patients presenting with this condition. Our series contained 34 patients with mutations in ACTB and only nine with ACTG1 mutations. Here, we report on seven unrelated patients with six mutations in ACTG1–four novel and two previously reported. Only one of seven patients was clinically diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 16 publications
(35 reference statements)
2
28
0
Order By: Relevance
“…Posterior partial SBH has been associated with mutations of LIS1 in about 30% of patients, with predominantly mosaic mutations. Short SBH are sometimes seen between regions of frontal pachygyria and normal posterior cortex in patients with BWCFF syndrome due to mutations of ACTB or ACTG1 [Di Donato et al, 2016b]. …”
Section: Discussionmentioning
confidence: 99%
“…Posterior partial SBH has been associated with mutations of LIS1 in about 30% of patients, with predominantly mosaic mutations. Short SBH are sometimes seen between regions of frontal pachygyria and normal posterior cortex in patients with BWCFF syndrome due to mutations of ACTB or ACTG1 [Di Donato et al, 2016b]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that ACTB mutations result in a more severe phenotype (2,7). Our observations indicate that a severe craniofacial phenotype has so far been associated with ACTB variants, whereas ACTG1 mutation carriers are more likely, although not consistently (17), to have a cortical brain malformation, hence also more severe ID and/or epilepsy. Indeed, the two foetuses described by Poirier et al (6) with microlissencephaly and facial features of BWCFF had novel mutations in ACTG1 (p.Ile75Leu and p.Pro343Ile).…”
Section: Mutation Spectrum and Genotype-phenotype Correlationmentioning
confidence: 60%
“…Therefore, it has been suggested that ACTB mutations result in a more severe phenotype 2,7 . Our observations indicate that a severe craniofacial phenotype has so far been associated with ACTB variants, whereas ACTG1 mutation carriers are more likely, although not consistently 17 , to have a cortical brain malformation, hence also more severe intellectual disability and/or epilepsy. Indeed, the two fetuses described by Poirier et al 6 with microlissencephaly and facial features of BWCFF had novel mutations in ACTG1 (p.Ile75Leu & p.Pro343Ile).…”
Section: Mutation Spectrum and Genotype-phenotype Correlationmentioning
confidence: 68%